Controle social : desafios e possibilidades da participação social garantir o cumprimento da democracia política no SUS - Bühler, Denise Nunes de Campos (2016)
The social control can be considered an advanced form of democracy to establish a new relationship between the state and society, so that decisions on actions in health must comply with common priorities and community interests. This study is guided by reflection on the possibility of a participatory management fact ensure compliance of political democracy in the SUS, consolidating its position as an effective practice. Aiming to analyze how to express social control in health advice, we decided to use the published research on the subject, which had empirical data reports. So build an overview of the actions of health advice on social control. The data collection analysis raised the question that how can an advanced, democratic proposal, highly politicized, to be put into practice very quickly be surrounded by practices that own proposal aimed to tackle. We left from there to the understanding of the proposed social control through the study of citizenship and democracy and the conditions of its application in Brazil. We conclude that health advice, despite the autonomy to propose and strategize and act to control and implementation of health policies, mostly not yet managed to take ownership of the fact of such practices. However, emerges the realization that a path is already being done and although in some cases this road show is tortuous, other can see the search for a compromise path to Public Health and general users.